The Influence of Incentive Provision on Employee Performance with Work Discipline as a Mediating Variable at PT. Pegadaian Branch Selong - Mitia Arisni Agustina; Djoko Suprayetno; Santi Nururly; Abbas, Jawad (Tinta Emas Publisher, 2023)
This research aims to determine the significance of the influence of incentive provision on employee performance with discipline as a mediating variable at PT. Pegadaian (State-Owned) Selong Branch. The population used in this study is all employees of PT. Pegadaian (State-Owned) Selong Branch, totaling 33 individuals. The research employed a causal associative approach with a quantitative method. Data collection was conducted using questionnaires. The data analysis tools utilized in this research were the outer model and inner model analyses through the Smart PLS version 3.0 software. The results of the study indicate that incentive provision has a positive and significant impact on the performance of employees at PT. Pegadaian (State-Owned) Selong Branch. Additionally, incentive provision has a positive and significant influence on the work discipline of employees at PT. Pegadaian (State-Owned) Selong Branch. Work discipline also has a positive and significant effect on the performance of employees at PT. Pegadaian (State-Owned) Selong Branch. Furthermore, incentive provision has a positive and significant impact on employee performance, with work discipline as a mediating factor at PT. Pegadaian (State-Owned) Selong Branch.